Applying Constructivist: Authentic Project-Based Learning for Increasing Performance in Writing Outcomes - Isnaniah Isnaniah; Lastry Forsia; Sholeh Hidayat (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
Writing is a complex and essential skill in English as a Foreign Language (EFL) learning that requires not only linguistic accuracy but also cognitive engagement, interaction, and reflection. This study aims to examine the relationship between constructivist writing instructional practices implemented through Authentic Project-Based Learning (A-PBL) and students? writing performance outcomes. Employing a quantitative quasi-experimental one-group pre-test?post-test design, the study involved 35 first-semester undergraduate students enrolled in a Writing course at Universitas Islam Syekh Yusuf. Data were collected through writing performance tests assessing contextual, interactive, and reflective writing, as well as a questionnaire measuring students? engagement in constructivist practices, including brainstorming, collaborative writing, peer feedback, real-world writing tasks, and instructional scaffolding. The data were analyzed using descriptive statistics, multiple regression analysis, and Canonical Correlation Analysis (CCA). The findings reveal a statistically significant multivariate relationship between constructivist learning practices and writing performance outcomes, with interactive and reflective writing emerging as the most strongly influenced dimensions. Although contextual writing did not show a direct significant effect, it functioned as a foundational component supporting higher-level writing engagement. The study concludes that constructivist-oriented writing instruction, particularly through A-PBL, effectively promotes interactive and reflective writing development and provides a theoretically grounded approach for enhancing EFL writing performance in higher education contexts.